2009
DOI: 10.1002/asna.200911225
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic system CH Cygni: An analysis of the shocked nebulae at different epochs

Abstract: Context. We analyse the line and continuum spectra of the symbiotic system CH Cygni. Aims. To show that the colliding-wind model is valid to explain this symbiotic star at different phases. Methods. Peculiar observed features such as flickering, radio variation, X-ray emission, as well as the distribution of the nebulae and shells throughout the system are investigated by modelling the spectra at different epochs. The models account consistently for shock and photoionization and are constrained by absolute flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 46 publications
(60 reference statements)
0
31
0
Order By: Relevance
“…During the 4.5 hours of continuous monitoring, V648 Car showed a remarkably large flickering with a recorded maximum amplitude of 0.63 mag, and with variations > 0.5mag over a period shorter than 15 minutes. To our knowledge, this is amongst the largest flickering ever reported from a symbiotic star, comparable to the flickering amplitude of the well-studied symbiotic CH Cyg during its 1998 active state (Sokoloski & Kenyon 2003, Contini et al 2009). …”
Section: Resultsmentioning
confidence: 88%
“…During the 4.5 hours of continuous monitoring, V648 Car showed a remarkably large flickering with a recorded maximum amplitude of 0.63 mag, and with variations > 0.5mag over a period shorter than 15 minutes. To our knowledge, this is amongst the largest flickering ever reported from a symbiotic star, comparable to the flickering amplitude of the well-studied symbiotic CH Cyg during its 1998 active state (Sokoloski & Kenyon 2003, Contini et al 2009). …”
Section: Resultsmentioning
confidence: 88%
“…As we have shown in previous papers (e.g. Contini et al 2009b), a few schematic models can describe the variable spectra of SSs: therefore, we compare the combination of models calculated by the fit of the line spectrum on the basis of a data set taken on a certain time, with a mosaic of continuum data observed at very different epochs. The modelling is presented in Fig.…”
Section: The Continuum Sedmentioning
confidence: 99%
“…Previous modelling of SSs in different phases of outburst and quiescence (Contini, Angeloni & Rafanelli 2009b; Angeloni et al 2007a, and references therein) led to recognize some main dynamical mechanisms that can be summarized by: the collision of the stellar winds which leads to shocked nebulae at different location on the orbital plane, the formation of a disc as a consequence of accretion phenomena, the ejection of jets and lobes perpendicular to the orbital plane, and the outburst of the WD at the origin of the blast wave propagation outwards in the interstellar medium (ISM). Furthermore, also the dust shells emitted by the Mira contribute to the line and continuum spectra and might be responsible for obscuration episodes.…”
Section: Introductionmentioning
confidence: 99%
“…11 During the past eruption phases, the blue continuum was believed to be produced due to the accretion disk (Yoo and Yamashita, 1984). However, Contini et al (2008) suggested the UV lines were formed in expanding shocked nebulae.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…In the eruption and quiescence phases, CH Cygni was observed on X-ray, UV, visible, IR and radio wavelengths (Yoo, 2006, Paper I, references in there). While the broadest emission component of H I lines was caused by bipolar radio jets (Paper I), Contini et al (2008) proposed the broadest emission component of H I lines was formed from downstream of a fast reverse shock.…”
Section: Introductionmentioning
confidence: 99%